The Sociological Meaning of Pregnancy and Baby Birth Ceremonies in Javanese People in Buntu Pane Village Asahan - Rholand Muary (Britain International for Academic Research (BIAR-Publisher), 2021)
Indonesia is an archipelagic country that has a variety of customs and habits. One of the customs and habits that exist in several places, namely cultural rituals during pregnancy and birth in Buntu Pane Village, is one of the villages that implements the Javanese tradition of pregnancy and birth ceremonies. This study aims to describe the process of a series of pregnancy ceremonies until delivery. In this study using qualitative methods, the method of collecting data by means of participatory observation, and in-depth interviews. In this study, several things were found, namely (1) traditional pregnancy ceremonies such as telonan and tingkeban. (2) Post-natal traditional ceremonies, namely brokohan, sepasaran and selapanan. (3) There is also a tradition of pounding bayen and baby chomping. (4) There is a symbolic meaning of offerings and offerings contained in a series of pregnancy and postpartum ceremonies. The conclusion in this study is the sociological meaning of all rituals and traditions that are believed and carried out only with the aim of gaining salvation to God Almighty. Besides that, it also preserves ancestral traditions and maintains balance and happiness in life, namely a safe and peaceful condition without interference from other creatures or the natural surroundings.